Análise do funcionamento discursivo de hashtags no twitter: o caso das hashtags #somostodosmacacos e #microcontos' - Neto, José Roque Damasco (2018)
The present thesis was based on studies on the relationship between the discursive functioning of the #common and #microcontos and the alienation of the ordinary subject of Twitter that circulate them. Thus the theoretical clipping was established on materialist bases, where the main readings were Marx, Althusser, Haroche, Rancière and Pêcheux so that we mobilized the concepts of alienation, ideological apparatuses of state, democracy and visibility. The discursive bases that guided the analysis were established mainly around the notions of repeatability, production of meanings, memory, normatization, ideology and subject, and subterranean cleavages. The choice of #microcontos and hashtag #somostodosmacacos was made by both having the crossing of the discursive formation media, because both circulate in the digital discursive environment of Twitter, which is characterized, predominantly, by the discourse of the writerality. However, the discursive analysis showed that #microcontos is characterized as a discourse of writing that circulates in this environment. This finding was possible from the cut of the corpus by the notion of authorship. On the other hand, we could consider the trending topics, or "subjects of the moment", as a way in which materializes the alienation of the subjects in relation to their discourse and to their work of producing polemics.